Pilot Study Assessing the Impact of Intrathecal Administration of Variants AAV-PHP.B and AAV-PHP.eB on Brain Transduction in Adult Rhesus Macaques - Arotcarena, Marie-Laure; Dovero, Sandra; Biendon, Nathalie; Dutheil, Nathalie; Planche, Vincent; Bezard, Erwan; Dehay, Benjamin (Frontiers in Bioengineering and Biotechnology, 2021)
Adeno-associated virus (AAV) vectors are increasingly used as an effective and safe approach to deliver genetic material to the central nervous system (CNS). The AAV9-derived variants, AAV-PHP.B and AAV-PHP.eB, reportedly broadly transduce cells throughout the CNS compared to the original serotype 9, AAV9. As non-human primate data are scarce, we here evaluated the CNS transduction efficiencies after lumbar intrathecal bolus delivery of identical doses of either AAV-PHP.B:CAG-EGFP or AAV-PHP.eB:CAG-EGFP in rhesus macaque monkeys. AAV-PHP.eB achieved a more efficient and widespread CNS transduction compared to AAV-PHP.B. We report a strong neuronal and oligodendroglial tropism for both variants in the putamen and in the hippocampus. This proof-of-concept experiment highlights the potential value of intrathecal infusions of AAV-PHP.eB to distribute genetic material in the CNS with cell-type specificity and introduces a new opportunity to model brain diseases in rhesus macaque monkeys and further develop gene therapies targeting the CNS in humans.